Pengaruh Penerapan Modul terhadap Hasil Belajar Siswa Kelas VII di SMP Negeri 3 Mepanga - Hadi Pramono; Mohammad Jamhari; Syech Zainal (Jurnal Kreatif Online, 2022)
This study aims to describe the effect of the application of modules in science learning on the learning outcomes of seventh grade students at SMP Negeri 3 Mepanga. This type of research is a quasi-experimental by forming two groups of research subjects, namely the experimental group using learning modules and the control group using student books in the learning process. The research design used was unreated control group design with dependent pretest and posttest samples. The results of this study indicate that there are differences in the average learning outcomes of experimental group students and control group students. The average experimental group student learning outcome of 79.54 and the average value of control group student learning outcomes is 73.04. This is evidenced by the value of Sig. (2-tailed) on a t-test smaller than 0.05, Sig. (2-tailed) 0.001 <0.05, thus H0 is rejected and Ha is accepted, which means that there is an effect of application of modules in science learning on the learning outcomes of seventh grade students at SMP Negeri 3 Mepanga.